DIVERSITY OF BUTTERFLY Lepidoptera IN THE CAMPUS AREA OF PATTIMURA UNIVERSITY AMBON MALUKU - Wakano, Delly; Moniharapon, Debby Dijola (Universitas Pattimura, 2019)
Butterflies are insects that belong to the order Lepidoptera, meaning insects whose body surface is almost entirely covered by sheets of scales that give the style and color of butterfly wings. Butterflies are generally active during the day. The purpose of this study was to determine the diversity of butterfly species that exist in the Pattimura University campus area, Ambon. This research was conducted in February 2018. This research was conducted at 4 stations with 2 count points for each station. The results of research in the Pattimura University campus area at each station found 20 species from 4 major families of butterflies with 322 individual butterflies in all stations. The diversity index for all stations is 2.54 and belongs to the category of moderate species diversity.